Pengaruh Game Kolam Ikan terhadap Keterampilan Berhitung Siswa Kelas II pada Materi Perkalian - Tarmini, Reni; Isrok’atun, Isrok’atun; Aeni, Ani Nur (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to determine the effect of the fish pond game on class II students' numeracy skills in multiplication material. This research uses a quasi-experimental design method with a non-equivalent control group whose population is class II students at SDN accredited A in Cimalaka sub-district. The samples from this research were class II students at SDN Citimun II and SDN Cimalaka III, each with a sample of 37 people. The instruments used are arithmetic skills tests, observation sheets, and documentation. Based on the research results, it shows that counting skills are positively and significantly influenced by the fish pond game. The results of the Independent Sample Test in the intervention group obtained a difference in the average pre-test and post-test scores with a ρ value of 0.012 < α 0.05, and the test results obtained an N-gain score of 0.56 and an N-gain percent of 56.17%. with moderate and quite effective categories, while learning using conventional media obtained an N-gain score of 0.44 and an N-gain percent of 43.65%. In conclusion, learning using fish pond games is more influential than using conventional media. Keywords: Counting Skills, Fish Pond Game, Multiplication Material